(untitled) (Stato, Chiese e pluralismo confessionale, 2016)
Contributo non sottoposto a valutazi SOMMARIO: 1. Introduzione - 2. I diritti sociali in Europa e il Comitato europeo sui diritti sociali (CEDS) - 3. Le decisioni di merito del Comitato europeo dei diritti sociali sull’attuazione nel nostro Paese della legge n. 194 del 1978 - 4. L’obiezione di coscienza e l’interruzione volontaria della gravidanza in Italia - 5. Le strade possibili per dare una sostenibilità pubblica all’obiezione di coscienza - 6. Alcune brevi considerazioni di sintesi. SUMMARY: The author examines the decision of the European Committee of Social Rights (CEDS), which once again condemned Italy had not taken our country, compared to the large number of doctors objectors, no organizational measures to ensure the reproductive rights of women and the right to work of non-objectors. He thus addresses the issue of social rights in Europe and the role of guarantor of the CEDS to focus eventually on conscientious objection, which considers a fundamental right, which must, however, know how to give, not interfere collectability of other rights. Moreover, it indicates, finally, what are the possible ways to give concrete and practical sustainability of conscientious objection.